IMPLEMENTASI ASESMEN SUMATIF MELALUI APLIKASI ZYA-CBTPADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS VIIIDI MADRASAH TSANAWIYAH NEGERI 1 WONOSOBO - Zulham Nugroho; Ruhadi; Tutik Wijayanti; Eni Rahmawati (Unnes Civic Education Journal, 2026)
Technological developments have driven the transformation of learning evaluation  from conventional systems to digital ones through Computer-Based Testing (CBT).  Consequently, MTsN 1 Wonosobo, through its policy, has implemented ZYA-CBT-based  summative assessment in the madrasah, specifically for the subject of Pancasila  Education, to enhance the practicality of summative assessment and ensure student  integrity. This study employs a qualitative descriptive approach with a field research..  Data were collected through observation, interviews, and documentation, then  analyzed via data reduction, data presentation, and conclusion drawing, utilizing  triangulation of sources and techniques to ensure data validity. The results of the study  indicate that the implementation of summative assessment using ZYA-CBT proceeded  effectively and systematically through the planning, implementation, and evaluation  stages. Thus, the use of ZYA-CBT at MTsN 1 Wonosobo can improve effectiveness,  efficiency, and objectivity, as well as strengthen students’ character of honesty through  direct supervision and via the system, although its implementation still faces challenges  related to the system, internet connectivity, and students’ device readiness.